Deconstructing ideological polarisation and moral incongruence in Gaza war media discourse: a critical discourse analysis - Abas, Nadhratunnaim (GADING Journal for the Social Sciences, 2024)
The Gaza War, which has been ongoing since 1947 and claimed countless lives, has generated many responses worldwide. Information about this discursive event has also been widely covered in the media. Mediated discourse tends to be ideological. Thus, ideas about the war can be ideologically embedded and constructed to manufacture consented opinions and beliefs. Additionally, although many studies have been conducted on the discourse related to the Israel-Palestine conflict, they have yet to look at the bridge between ideology and moral stance. This is because, as discourse constructs social actions, it is important to uncover the semantic macrostructures within the boundary of morality. The study examines two online news editorials, each expressing a pro-Israeli or pro-Palestine stance. Based on van Dijk's ideological polarisation, the study finds that ideological polarisation does take place in the two articles examined through the discursive strategies of emphasising 'Our' good / 'Their' bad properties or actions and mitigating 'Our' bad / 'Their' good properties or actions. In this case, the Israelis are positively represented as the in-group and the Palestinians are negatively portrayed as the out-group in Article 1 which expresses the ideology of pro-Israelis. However, in Article 2, which expresses the ideology of pro-Palestinians, the Palestinians are positively represented as the in-group and the Israelis are negatively depicted as the out-group. The good and bad properties or actions reflect the moral stance of each side. As Article 1 supports physical violence to avenge their opponents although it condemns terrorism, the mismatch between their ideology and moral stance indicates moral incongruence. However, as physical violence is not mentioned as a way to avenge the opponents, Article 2 tends to remain morally congruent. The study contributes to the vast literature on ideological polarisation in the media representation of the Israel-Palestine conflict with additional insight into how the conflicting ideology, moral stance and a discursive event may suggest moral incongruence.